2014
DOI: 10.3109/09540261.2014.890922
|View full text |Cite
|
Sign up to set email alerts
|

The role of spirituality in coping with the demands of the hospital culture amongst fourth-year nursing students

Abstract: The aim of this research was to describe the role of spirituality in coping with the demands of the hospital culture amongst fourth-year nursing students. Qualitative, descriptive, hermeneutic interpretive research was done. A case study of 14 female Canadian nursing students was asked to write an essay on their experiences of the demands of the hospital culture. Content analysis was used and positive psychology served as the interpretive lens. Trustworthiness and ethicality were ensured. The findings indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Nursing educators must establish strategies to enhance self‐efficacy based on professional values. Recently, nursing research has focused on spirituality as a reflective tool for enhancing self‐efficacy and allowing people to deal with difficult situations (Puchalski & Guenther , Cilliers & Terblanche , Adegbola ). Senior nursing students are going to become nurses and meet with difficult patients in diverse situations very soon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing educators must establish strategies to enhance self‐efficacy based on professional values. Recently, nursing research has focused on spirituality as a reflective tool for enhancing self‐efficacy and allowing people to deal with difficult situations (Puchalski & Guenther , Cilliers & Terblanche , Adegbola ). Senior nursing students are going to become nurses and meet with difficult patients in diverse situations very soon.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing educators should develop specific curricula to help senior nursing students in the transition to professional life, before they go to work in hospitals. Recently, nursing research has become interested in spirituality as a means of helping people develop self‐efficacy and be able to deal with difficult situations (Puchalski & Guenther , Cilliers & Terblanche , Adegbola ). Spirituality is defined as an individual pursuit for meaning and purpose in life and transcendental truth, including a sense of connectedness with the self, others and the world (Puchalski & Guenther ).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the recommended interventions refer to improvements of potentially strenuous work conditions such as high work load (e.g., Rabin et al, 2011) or generally adverse working conditions (Malinauskiene et al, 2011). On the other hand, support of individual staff members is recommended in form of supervision (Berg & Hallberg, 1999;Palsson et al, 1994), mentoring (Cilliers & Terblanche, 2014), mindfulness meditation (Foureur, Besley, Burton, Yu, & Crisp, 2013), training and peer support (Michael & Jenkins, 2001), or targeted support for staff with burn-out symptoms (Tselebis et al, 2001). Some authors also recommend a combination of organization-and individual-related interventions (e.g., Cilliers, 2003;Reid et al, 2004) as both may contribute to a better use of coping resources (Lewis et al, 1994).…”
Section: Implications For Occupational Health In Hospitalsmentioning
confidence: 99%
“…Participants were asked to write an essay based upon their hospital experiences. Trustworthiness of the data was secured, and the findings demonstrated that students did not demonstrate spiritual intelligence; rather, internal conflict was evident and spiritual coping did not transpire [22,24].…”
Section: Spirituality and Resilience Development In Prelicensure Nursmentioning
confidence: 99%